Incremental Value of Two Dimensional Speckle Tracking Echocardiography in the Functional Assessment and Characterization of Subclinical Left Ventricular Dysfunction - Gunasekaran, Prasad (Curr Cardiol Rev, 2017)
Subclinical left ventricular (LV) dysfunction refers to subtle abnormalities in LV function which typically precede a reduction in the left ventricular ejection fraction (LVEF). The assessment of myocardial function using LVEF, a radial metric of systolic function, is subject to load dependence, intra-observer and inter-observer variability. Reductions in LVEF typically manifest late in the disease process thus compromising the ability to intervene before irreversible impairment of systolic perfor-mance sets in. 2-Dimensional speckle tracking echocardiography (2D-STE), a novel strain imaging modality has shown promise as a sensitive indicator of myocardial contractility. It arms the clinician with a powerful and practical tool to rapidly quantify cardiac mechanics, circumventing several inherent limitations of conventional echocardiography. This article highlights the incremental utility of 2D-STE in the detection of subclinical LV dysfunction.